Comparative study of totally extra-peritoneal hernia repair versus open Lichtenstein hernioplasty for the treatment of primary inguinal hernia - Kara, Yasin (Journal of Surgery and Medicine, 2019)
Aim: There is still controversy over which inguinal hernia repair technique has the best postoperative results. Totally extra-peritoneal hernia (TEP) repair was compared with conventional open Lichtenstein (OL) herniorrhaphy in terms of postoperative pain, return time to work, recurrence rates and complications. Methods: In this predesigned comparative study, total number of 97 patients who underwent TEP or Lichtenstein herniorrhaphy in Health Sciences University, Kanuni Sultan Süleyman Education and Research Hospital, in between January 2018 and September 2018 were evaluated and compared. Patients were divided in two groups as TEP group (n:50) and OL group (n:47). Demographic properties (age, sex), operation time, postoperative pain, hospital stay, return to work, recurrence rates and/or complications were analyzed and compared with each other. Results: The mean operation time was 55.7 (19.90) minutes in TEP group, while it was 39.44 (10.69) minutes in OL group (P=0.001). Postoperative pain with VAS in TEP group on the first postoperative day was 3.2 (1.12) (range: 2-6), while it was 5.6 (1.02) (range: 2-8) in the OL group (P=0.001). The average time return to their routine work ranged from 6-18 days (mean 9.2 (2.03) in TEP group while it was 7-26 days (mean 14.8 (3.1)) in OL group (P= 0.001). Postoperative complications as urinary retention, seroma, hematoma formation and paresthesia sensation were higher in OL group. Conclusion: In our study, TEP repair was superior to OL repair in terms of postoperative pain, early return to work, chronic pain, postoperative urinary retention, seroma formation and postoperative paresthesia sensation. More studies with large case series and longer follow-up periods are still needed to judge the role of laparoscopy in repairing inguinal hernias.